Quantum Chemical Calculation and DFT Study of Sitagliptin: Insight from Computational Evaluation and Docking Approach - Chaudhary, M. K.; Prajapati, P.; Joshi, B. D. (Journal of Nepal Physical Society, 2020)
This study aims to explore the structural and chemical behavior of sitagliptin using density functional theory (DFT). The chemical reactivity has been studied in terms of MEP, HOMO-LUMO energy gap, Hirshfeld charge, and global and local reactivity descriptors. Thermodynamic parameters like entropy, enthalpy and specific heat capacity and, nonlinear optical (NLO) properties have been analysed. Higher value of the first hyperpolarizability than that of urea show its potential use as NLO material. Intra-molecular Hydrogen bonding and topological parameters at the bond critical point (BCP) of title molecule have been studied by using the quantum theory of atoms in molecules (QTAIM) approach. The bond of 2.3777 Å between H42…N11 is noticed to be strongest one. The pharmacological behavior and protein-ligand interaction of the title molecule have been investigated in terms of drug-likeness and molecular docking which motivates that the amine and carbonyl group bind with the amino acid of the protein.